2019
DOI: 10.1021/acsaem.8b01819
|View full text |Cite
|
Sign up to set email alerts
|

Effective Electrochemical Charge Storage in the High-Lithium Compound Li8ZrO6

Abstract: is a pseudolamellar compound with high lithium content. Even though it is intrinsically a poor conductor and does not contain a transition metal with easily variable oxidation states, a new synthetic approach to preparing it in nanocomposite form with intimate contact to a conductive carbon by mechanical delamination enabled galvanostatic cycling of coin halfcells containing Li 8 ZrO 6 /C as the cathode and Li metal as the anode at 221 mAh/g (which corresponds to extracting 2 Li per formula unit) over at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 70 publications
1
26
0
Order By: Relevance
“…For the (0001) surface, we considered several configurations, and their average delithiation energies and the energy differences between the HS state and NSP state are listed in Table 5. By and large, the surface with T3 (22) and T3 (44) removed has the lowest average delithiation energy (3.32 eV), indicating that lithium removal is more likely to occur at the surface than in the bulk.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
See 1 more Smart Citation
“…For the (0001) surface, we considered several configurations, and their average delithiation energies and the energy differences between the HS state and NSP state are listed in Table 5. By and large, the surface with T3 (22) and T3 (44) removed has the lowest average delithiation energy (3.32 eV), indicating that lithium removal is more likely to occur at the surface than in the bulk.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…Because Sn­(IV) has a full d subshell, we expect only anionic oxygen redox in LSO. , We have previously studied Li 8 ZrO 6 (LZO), which is also a solely anionic-redox cathode material. The electron transport mechanism in LZO mainly involves small-polaron diffusion of oxygen polarons. By replacing the transition metal Zr with the main-group metal Sn, we obtain a material (LSO) that was found as a stable lithiated phase of SnO 2 in experiments. Previous DFT calculations of different lithiated tin-based oxides were carried out mainly for predicting the binding energies of Sn 3d 5/2 to elucidate the core level chemical shift observed in the XPS measurement . However, the effect of delithiation in Li 8 SnO 6 on the electrochemical performance of tin-oxides as the cathode in the lithium-ion battery is not yet well-understood in the above-mentioned literature.…”
Section: Introductionmentioning
confidence: 99%
“…The redox reactions of LMO during the charging processes are discussed here. In our previous experimental and theoretical studies on LZO, which is isostructural with LMO, it was shown that the delithiation in LZO occurs topotactically without a phase change . Therefore, the present study considered the topotactic mode of removing Li from Li 8 MnO 6.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Anionic redox in Li-excess layered oxides offers not only additional capacity but also higher voltage (above 4.0 V). Oxygen redox has also been found in other Li-excess layered oxides: Li 8 ZrO 6 , Li 8 SnO 6 , Li 2 –x Ru 1–y Sn y O 3 , Li 2 MnO 3 , Li 4 FeSbO 6 , Li 5 FeO 4 , Li 3 NbO 4 , and Li­(Li 0.17 Ni 0.17 Fe 0.17 Mn 0.49 )­O 2 . , A downside of the increased capacity is the requirement of controlling the voltage range to prevent further redox reactions of O – that may cause irreversible electrochemical deterioration like capacity loss, voltage hysteresis, structural failure, or even the release of oxygen gas. Oxygen gas release may trigger severe thermal runaway caused by exothermic reaction with the electrolyte and/or anode material, , and this seriously impedes the safe realization of high energy density and voltage with Li-excess layered oxides.…”
Section: Introductionmentioning
confidence: 99%
“…As the key component of an electrolyte, many salts have been reported for rechargeable batteries, such as hexafluorophosphate (MPF 6 ) [14] , bis(fluorosulfonyl)imide (MFSI) [15,16] and trifluoromethanesulfonate (MCF 3 SO 3 ) salts [17] . The composition of metal salts plays a key role in the stability of batteries, especially the anions in salts that regulate the thermodynamic stability of the electrolyte.…”
Section: Metal Salt Regulationmentioning
confidence: 99%